Racial Truth-Telling in Dual Enrollment: Exploring Organizational Constraints and Possibilities in the Anti-CRT Era - Julia C. Duncheon; Suneal Kolluri; Dustin Hornbeck (AERA Open, 2025)
K–12 teachers have become targets of political censorship in many states, with anti-CRT laws designed to eliminate racial truth-telling, or curricular content related to race and racism. Higher education has been targeted as well, most recently with anti-DEI initiatives, but college professors generally retain more curricular autonomy than their high school counterparts. As such, dual enrollment (DE)—college coursework delivered to high school students through a partnering postsecondary institution—may provide an avenue for students to learn about race and racism. Through the lens of racialized organizations, this study uses case study methodology to explore how a community college in Texas constrains or enables racial truth-telling in its DE courses. The findings show how the college’s ostensibly race-neutral response to K–12 curricular censorship placed the burden to defend racial truth-telling on individual DE faculty, with implications for their ability to do it. The paper closes with recommendations for policy and practice.